ALISIS PENDIDIKAN KARAKTER DALAM GEGURITAN DHARMA SUNYATA TERHADAP REMAJA MASA KINI DI DESA DUKUH PENABAN KARANGASEM - I Wayan Adi Upadana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
ABSTRACTThe results of this study structurally of Geguritan Dharma Sunyata consist of forma structure and narrative structure. Forma structure includes: a code language and literature, language diversity, language style and sasminitaning tembang. Narrative structure includes: characterizations figures, background or setting, theme and mandate. Character education contained in Geguritan Dharma Sunyata consists of divinity field character education includes a religious character, the character of tolerance and honest character. Character education humanitarian fields consists of peace-loving character, discipline, hard work, curiosity, recognize achievement and responsibility. Character education environment field the character of environmental care. The function of character education in Geguritan Dharma Sunyata to today's youth in the village of Dukuh Penaban Karangsem is as the character formation of divinity, the social character and the love of environmental character that source in the teachings of Tri Hita Karana and mental revolutionized young people to have a good moral behavior.Keywords: Character Education, Geguritan Dharma Sunyata, and Today's Youth